Biweekly combination of trastuzumab, docetaxel and gemcitabine for HER2-positive metastatic breast cancer: results of a Phase II GOIM study. (April 2014) - Orlando, Laura; Giotta, Francesco; Lorusso, Vito; De Vita, Ferdinando; Filippelli, Gianfranco; Maiello, Evaristo; Riccardi, Ferdinando; Pappagallo, Giovanni Luigi; Fedele, Palma; Gebbia, Nicola; Verderame, Francesco; Barni, Sandro; et al.
ABSTRACT: : Aims: Clinical activity of chemotherapy plus trastuzumab in HER2 overexpressing advanced breast cancer has been documented. We report the activity and safety results of biweekly combination of trastuzumab, docetaxel and gemcitabine as first-line therapy in HER2-positive advanced breast cancer.Patients & methods: Patients were biweekly treated with trastuzumab (4 mg/kg), gemcitabine (1000 mg/m 2 ) and docetaxel (50 mg/m 2 ). The primary end point was overall response rate, secondary time to progression, clinical benefit rate (partial response plus complete response plus stable disease for ≥ 24 weeks) and tolerability.Results: A total of 65 patients with HER2-positive advanced breast cancer have been enrolled. In total, 47 patients responded (73%; 95% CI, 60–84), 11 achieved complete response (17%; 95% CI: 8.9–28.7), 36 achieved partial response (56%; 95% CI: 43–68.6). The clinical benefit rate was 87.5% (95% CI: 77–94). Three patients (4.7%) experienced progressive disease. The median time to progression was 14.2 months (95% CI: 10.6–17.8), the median overall survival was 39.3 months and the 36-month survival rate was 55.5% (95% CI: 58–73). The worst toxicities were grade 3 neutropenia (12%), thrombocytopenia (6%) and diarrhea (6%). No cardiac toxicity was reported.Conclusion: As first-line therapy, this combination allowed the delivery of polychemotherapy in association to targeted therapy, with clinical activity and mild toxicity. The promising results should be further explored in Phase III randomized clinical trials.